Asymmetric evolutionary responses to sex‐specific selection in a hermaphrodite. (10th September 2018) - Bonel, Nicolás; Noël, Elsa; Janicke, Tim; Sartori, Kevin; Chapuis, Elodie; Ségard, Adeline; Meconcelli, Stefania; Pélissié, Benjamin; Sarda, Violette; David, Patrice
Abstract: Sex allocation theory predicts that simultaneous hermaphrodites evolve to an evolutionary stable resource allocation, whereby any increase in investment to male reproduction leads to a disproportionate cost on female reproduction and vice versa. However, empirical evidence for sexual trade‐offs in hermaphroditic animals is still limited. Here, we tested how male and female reproductive traits evolved under conditions of reduced selection on either male or female reproduction for 40 generations in a hermaphroditic snail. This selection favors a reinvestment of resources from the sex function under relaxed selection toward the other function. We found no such evolutionary response. Instead, juvenile survival and male reproductive success significantly decreased in lines where selection on the male function (i.e., sexual selection) was relaxed, while relaxing selection on the female function had no effect. Our results suggest that most polymorphisms under selection in these lines were not sex‐antagonistic. Rather, they were deleterious mutations affecting juvenile survival (thus reducing both male and female fitness) with strong pleiotropic effects on male success in a sexual selection context. These mutations accumulated when sexual selection was relaxed, which supports the idea that sexual selection in hermaphrodites contributes to purge the mutation load from the genome as in separate‐sex organisms.